2008
DOI: 10.1021/ac702060j
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Determination in the Low Nanogram per Liter Level of Different Classes of Drugs of Abuse in Sewage Water by On-Line Solid-Phase Extraction-Liquid Chromatography−Electrospray-Tandem Mass Spectrometry

Abstract: The present work describes the first fully automated method, based on on-line solid-phase extraction (SPE)-liquid chromatography-electrospray-tandem mass spectrometry, developed for the determination of drugs of abuse (17 compounds and metabolites belonging to the classes of amphetaminics, cannabinoids, cocainics, opiates, and lysergics) in sewage waters. On-line SPE is performed by passing 5 mL of the water sample through a PLRP-s cartridge for analytes measured in positive ionization mode (all but cannabinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
159
1
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(183 citation statements)
references
References 11 publications
14
159
1
9
Order By: Relevance
“…Opioids are present in surface water at lower concentrations than BE and COC (Postigo et al 2008b). The measured concentrations of METH in surface water from 36 rivers in China were in accordance with earlier reported levels (range <0.2-2.87 ng L −1 ) in surface water from Spain (Maria et al 2008;Postigo et al 2008a), Switzerland, British, and Italy (Zuccato et al 2008). However, the detection frequency of METH in this study is higher than that in European countries (Baker and …”
Section: Comparison With Other Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…Opioids are present in surface water at lower concentrations than BE and COC (Postigo et al 2008b). The measured concentrations of METH in surface water from 36 rivers in China were in accordance with earlier reported levels (range <0.2-2.87 ng L −1 ) in surface water from Spain (Maria et al 2008;Postigo et al 2008a), Switzerland, British, and Italy (Zuccato et al 2008). However, the detection frequency of METH in this study is higher than that in European countries (Baker and …”
Section: Comparison With Other Studiessupporting
confidence: 91%
“…In recent years, many studies have reported the occurrence and levels of illicit drugs and their metabolites in natural waters, especially in Europe (Baker and Kasprzyk-Hordern 2013;Fedorova et al 2014;Koeck-Schulmeyer et al 2011;Postigo et al 2008a;Postigo et al 2010;Rosa Boleda et al 2009;Vazquez-Roig et al 2013). Two cocainic compounds, cocaine (COC) and its metabolite benzoylecgonine (BE), have high detection frequencies and occur at high levels in the surface waters of Europe.…”
Section: Responsible Editor: Ester Heathmentioning
confidence: 99%
“…15 Exceção é feita em estudos envolvendo o LSD, nos quais é também investigada a ocorrência de dois metabólitos gerados a partir do consumo da droga, ou seja, o Nor-LSD e o 2-oxo-3-hidroxi-LSD (O-H-LSD). [17][18][19] A mescalina (MES), um dos poucos alucinógenos naturais deste grupo, também vem sendo recentemente estudada. 19 …”
Section: Estimulantes Anfetamínicos E Outras Substâncias Alucinógenasunclassified
“…Postigo e colaboradores 17 descreveram o primeiro método baseado na extração SPE acoplada a um cromatógrafo líqui-do equipado com um espectrômetro de massas in tandem (LC-MS/ MS). Esse tipo de configuração apresenta algumas vantagens quando comparada à SPE off-line, tais como minimização de problemas relacionados à contaminação da amostra, menor exposição do analista a materiais perigosos (solventes orgânicos, por exemplo) e menor consumo de solventes e de amostra.…”
Section: Preparo De Amostrasunclassified
See 1 more Smart Citation